Rekabentuk pembungkusan kuih Zheng Dong Bing - Wong, Mee Ung (Universiti Malaysia Sarawak (UNIMAS), 2014)
"Zheng Dong Bing" is a sweet bun that well knows among Chinese-Foochow. This study aims is to identify the packaging design problem facing by "Zheng Dong Bing" bun. The findings of this study will be used to design a new package that is suit the physical characteristic of"Zheng Dong Bing" bun in order to produce a new, fresher and more informative image for it. This also includes the study on materials that can be used in desiging packaging for fresh "Zheng Dong Bing" bun